The functional unity of the singing voice - Doscher, Barbara M., 1922-1996 (Scarecrow Press, 1994)
"An understanding of how the singing voice functions should be a prerequisite for all those who wish to teach singing. And fundamental to any safe and efficient teaching method is the recognition that the singing voice is a functional unit. Consequently, this second edition, like the first, describes the anatomy and physiology of breathing and phonation and examines the acoustical laws necessary for an understanding of resonation. It is designed primarily as a textbook for college vocal pedagogy courses. The updated edition includes more detailed illustrations and an expansion of the appendix on vocal misuse and abuse, including data on subglottic air pressure/air flow ratios, the phonatory mode known as belting, and the aging voice, especially as it is affected by hormonal changes in the body."--Publisher's description